Intrinsic and Extrinsically Limited Thermoelectric Transport within Semiconducting Single‐Walled Carbon Nanotube Networks. (28th February 2019) - Blackburn, Jeffrey L.; Kang, Stephen D.; Roos, Michael J.; Norton‐Baker, Brenna; Miller, Elisa M.; Ferguson, Andrew J.
Abstract: Doped networks of semiconducting single‐walled carbon nanotubes (s‐SWCNTs) have recently demonstrated high thermoelectric (TE) power factors and figures of merit. Efforts to further improve the TE performance of s‐SWCNT networks hinge upon deeper understanding of the mechanisms underlying charge transport. This study explores the dependence of conductivity, thermopower, and resulting TE power factor on carrier density and temperature in s‐SWCNT networks. Careful control of charge‐carrier density illustrates a distinct transition between transport that is limited by energetic barriers between nanotube bundles to an "intrinsic" regime where these barriers are small enough to reveal the intrinsic transport mechanism of the nanotubes. Transport is activated in the s‐SWCNT networks, although a critical survey of the literature demonstrates that the activation energies in s‐SWCNT networks are appreciably smaller than typical semiconducting polymers. At high conductivity, transport behavior is consistent with deformation potential scattering. The analysis demonstrates that mitigation of the "extrinsic" limitations to transport (e.g., inter‐nanotube junctions), and the concomitant reduction of conductivity activation energies, can lead to at least a doubling of the TE power factor. Further comparison to prototypical semiconducting polymers demonstrates that this strategy likely represents a general design principle for improving the TE performance of organic materials. Abstract : At high charge‐carrier densities, thermoelectric transport in doped semiconducting single‐walled carbon nanotubes (s‐SWCNTs) is governed by the intrinsic electronic properties of the s‐SWCNTs. In contrast, energetic barriers between nanotubes appear to limit carrier transport at low carrier densities. The minimization of these extrinsic transport barriers emerges as a general design principle for organic thermoelectric material performance.